Post COVID-19 and Crime Rate: A Case Study of KP (Pakistan) (Journal of Asian Development Studies, 2023)
Throughout history, human beings have seen a society that did not face the issues of crime and poverty. Poverty is one of the most significant causes of corruption in a community. However, the emergence of the COVID-19 pandemic disrupted established societal patterns, including the dynamics of crime. This study focused on the Khyber Pakhtunkhwa (KP) province and adopted a descriptive, questionnaire-based research approach, collecting responses from a sample size 6,341. The study results show that the crime rate has increased in post-COVID-19, compared to pre-COVID-19 situation. The crime rate did not increase in the specific region (KP) but rose in almost every part of Pakistan. The study suggests that if the KP government and institutions control inflation, drug supply, and other illegal activities, the crime rate will inevitably decline.